Peran Kompensasi dalam Mencapai Kesejahteraan dan Kepuasaan Kerja Karyawan - Dwi Erni Mazro’atul Ilmiyah; Siska Novy Isaroh; Lintang Cahya Kusuma; Nafia Ilhama Qurrotu’aini (Universitas 45 Surabaya, 2025)
Compensation plays an important role in human resource management as a strategic element to improve employee well-being and job satisfaction. This study aims to explore the relationship between compensation, well-being, and job satisfaction. The method used is qualitative with a library research approach, utilizing relevant academic literature. The results show that fair, competitive, and integrated compensation management with career development can increase employee motivation, loyalty, and productivity. In addition, the role of labor unions and transformational leadership also support the effectiveness of compensation policies. In conclusion, strategically designed compensation is able to meet employee needs and support the achievement of organizational goals.